Dupla metamorfose: O vampiro de Curitiba de Dalton Trevisan - Carvalho, Lílian Nunes da Silva (2009)
The purpose of this dissertation is to analyze how Dalton Trevisan s motifs like double and the myth of the vampire shaped the journey of the protagonist Nelsinho. O Vampiro de Curitiba contains these issues. to be analyzed. We believe that Nelsinho suffers an inner conflict because of being both the subject and the object of his own anxieties; therefore he assumes the role of a vampire in order to obtain sexual satisfaction by means of seduction. We started by reflecting on this duality and what else characterizes him. In the case of a diffuse subject we chose to look at the protagonist from the perspective of Sigmund Freud and Carl Gustav Jung. We noticed that in the Freudian perspective, double rises from the conflict between two psychic instances, the Id and Superego. The first one is impulsive and the second is repressive. The Ego acts as the mediator and is responsible for doing what the winner demands. The issue about double is related to the Unheimlich, a term used by Freud to describe the ambivalence between what is known and what is unknown. To Jung the approach to duality occurs through a self-regulatory system responsible for the oscillation between opposite poles; that is, the conscious (persona) and unconscious (shadow). These poles are used to characterize the integration of the personality of the human being. Then we argued the function of myth and the origin of the myth of the vampire, because such a discussion is necessary in order to understand the relationship between the characters Dracula and Nelsinho: Dracula needs blood to keep alive and Nelsinho needs sex in order not to die. As the author does not show us their stories in linear sequences, we also analyze the characters by reading several stories and piecing together the fragments of the character we found in each story. We conclude that Nelsinho is a dual person because he always lives the antagonism which makes him to be with between being both a subject and an object of love relationships. He is linked to the vampire just by looking for the element that keeps him alive